Методи тестування вразливостей бездротових мереж на базі Kali Linux - Завгородній, Я. О. (ХНУРЕ, 2024)
Wireless networks have become ubiquitous. They are used worldwide in various aspects of life: at home, at work, and in public places to connect to the Internet and conduct business or personal matters. Despite all the advantages of streamlining business and life, there are certain drawbacks in the form of risks. The insecurity of wireless networks has caused many problems in terms of intrusions into banks, companies, and government organizations. The frequency of these attacks only increases as network administrators are not fully aligned when it comes to securing wireless networks. The report discusses the Kali Linux operating system, specifically the built-in tools that can be used to test the vulnerabilities of wireless networks.
Keywords: Kali Linux; тестування вразливостей бездротових мереж